X-ray fluorescence scannings of a composite sediment core from Laguna Vogt, central west Patagonia - Carolina Franco; Antonio Maldonado; Christian Ohlendorf; Andrea Catalina Gebhardt; María Eugenia de Porras; Amalia Nuevo-Delaunay; César Méndez; Christoph Vogt; Bernd Zolitschka (PANGAEA, 2025)
A 3 m-long sediment composite record was retrieved from Laguna Vogt (46.74 S, central west Patagonia) using a UWITEC gravity corer (for the uppermost 70 cm depth) and a modified Livingstone piston corer (for the remaining depths) during march, 2020. Several analytical techniques were applied to the sediment records. Firstly, X-ray fluorescence and magnetic susceptibility scanning were done at 1 mm and 1 cm resolution, respectively. Afterwards, subsampling was carried out at a 1 cm depth resolution. Exceptionally, the resolution was changed to 0.5 cm for sections with contrasting lithologies. Bulk chemistry measurements for elements C, N, and S were performed on the subsamples at intervals between 4 and 0.5 cm. Finally, grain size distributions for the subsamples were measured using a 4 cm step protocol. Results are presented with respect to depth and age. Ages were derived from an age-depth model based on 9 samples taken for radiocarbon dating from the composite profile.